Veterinary communication skills and training in the United Kingdom and the United States of America - McDermott, Michael P. (2018)
Veterinary communication is a core clinical skill and is believed to have a positive impact on client satisfaction, trust and adherence to patient management recommendations. Veterinary communication skills training has therefore been incorporated into veterinary undergraduate and postgraduate education. This thesis focuses on the topic of veterinary communication and comprises two studies. The aim of the first study was to gain a current understanding of the state, adequacy, and relevance of veterinary communication skills and training in the United Kingdom (UK) and United States of America (USA). This was done by conducting a survey of a sample of veterinary surgeons in each country about communication skills and training in the context of a veterinary consultation. A quantitative and qualitative analysis of the data from the survey was undertaken. Key findings were that 98 percent of respondents (1,708/1,748) believed communication skills to be equal in importance to, or more important than, clinical knowledge, whereas only 40 percent (705/1,759) were interested in further communication skills training. Barriers to participation in communication CPD appear to include lack of time and/or employer support, and a belief among some practitioners that communication training could no longer benefit them or was inadequately matched to real-world communication challenges. The aim of the second study was to assess several factors that may impact on communication dynamics during a consultation. Fifty-five video-recorded veterinary consultations in the UK and USA were analysed as follows: 1. The complexity of the consultations was assessed using a tool previously validated for recording information via direct observation of consultations. Elements recorded included details on the patient(s) and reasons for the visit, problems investigated, body systems involved, tests performed, diagnoses, and outcomes. Categorical data statistics were recorded as whole numbers and percentages and Chi-Square calculations were done to measure differences between UK and USA data. Continuous data statistics were recorded as median, range, and interquartile ratio (IQR) and Mann-Whitney U tests were performed to measure UK versus USA differences. (Continuous data for the remaining elements in the study were analysed in the same manner.) Key findings were that consultations were complex, involving multiple problems, body systems, tests, diagnoses, and outcomes. 2. Consultations were analysed for alignment with two consultation models, the Calgary-Cambridge Model for Veterinary Consultations (GCCVM) and the Patient-centred Clinical Method, by coding elements of each consultation model in the consultation transcripts. The frequency and proportion of model elements demonstrated in each consultation were assessed, as was the alignment of the consultations to each model, defined by the percent of possible model elements demonstrated in each consultation. There was 86.67% alignment with the GCCVM and 62.50% alignment with the Patient-centred Clinical Method. Veterinary surgeons in the study spent more time gathering information and explaining than empathising or soliciting client input. 3. Consultations were also analysed for dominance of medical versus lifeworld dialogue using the Mishler Discourse Analysis, and medical dialogue dominated over lifeworld dialogue (65.62% to 34.48%). 4. Client/relationship centredness was evaluated using a novel application of a tool in veterinary communication research, the Verona Patient-centred Communication Evaluation Scale (VR-COPE). Results suggested a relatively high degree of client/relationship centredness (a median score of 76/100), though with somewhat lower scores for elements related to client emotions and the veterinary surgeon responding to them. 5. Client satisfaction was evaluated using the previously validated Client Satisfaction Quotient (CSQ). There was a high degree of satisfaction expressed by clients (median score of 94/114), though average scores were slightly lower for topics related to cost and expression of interest in the client’s opinion. Limitations of the research included the low response rate of US veterinary surgeons to the survey, the small, convenience-based sample used in the consultation study, the reliance on the researcher for maintaining quality and validity, and the scoring of client/relationship-centredness with a tool that heretofore had not been used in veterinary medicine and was not subjected to extensive inter-rater variability testing. The findings in this thesis support the contention that communication skills are important for veterinary practitioners. The work also highlights the need for making communication training a priority in undergraduate veterinary education and an accessible and relevant component of postgraduate CPD. The findings also suggest a need to equip veterinary students and practitioners for communication during consultations that are relatively complex with highly iterative flow between topics, as well as for addressing emotions and inviting input of clients. Elements of the GCCVM and other models may help provide a framework for training in these competencies.